ER stress: an emerging regulator in GVHD development - Choi, Hee-Jin; Yu, Xue-Zhong (Frontiers in Immunology, 2023)
Allogeneic hematopoietic cell transplantation (allo-HCT) is a promising therapeutic option for hematologic malignancies. However, the clinical benefits of allo-HCT are limited by the development of complications including graft-versus-host disease (GVHD). Conditioning regimens, such as chemotherapy and irradiation, which are administered to the patients prior to allo-HCT, can disrupt the endoplasmic reticulum (ER) homeostasis, and induce ER stress in the recipient's cells. The conditioning regimen activates antigen-presenting cells (APCs), which, in turn, activate donor cells, leading to ER stress in the transplanted cells. The unfolded protein response (UPR) is an evolutionarily conserved signaling pathway that manages ER stress in response to cellular stress. UPR has been identified as a significant regulatory player that influences the function of various immune cells, including T cells, B cells, macrophages, and dendritic cells (DCs), in various disease progressions. Therefore, targeting the UPR pathway has garnered significant attention as a promising approach for the treatment of numerous diseases, such as cancer, neurodegeneration, diabetes, and inflammatory diseases. In this review, we summarize the current literature regarding the contribution of ER stress response to the development of GVHD in both hematopoietic and non-hematopoietic cells. Additionally, we explore the potential therapeutic implications of targeting UPR to enhance the effectiveness of allo-HCT for patients with hematopoietic malignancies.